Isolation and Screening of Biosurfactant Producing Microorganisms from Hydrocarbon Contaminated Soils from Automobile Workshop - Santhini, K (International Journal of Pharmaceutical & Biological Archive, 2014)
Isolation and Screening of Biosurfactant Producing Microorganisms from Hydrocarbon Contaminated Soils from Automobile Workshop